Effect of plating parameters on the intrinsic stress in electroless nickel plating - Chen, Zhong (2012)
With the increasing application of electroless nickel (EN) as a bumping or under-bumping metalization material, the microelectronic packaging engineers are required to have a deeper understanding and control of intrinsic stress in EN plating. The purpose of this work is to investigate the effect of some of the most important operating parameters on the formation of intrinsic stress during plating. The analysis of variances method was applied to obtain both single effects and compound effects of selected factors. Results indicate that high pH value and aged solution affect the intrinsic stress significantly, while surface roughness does not have much influence on the intrinsic stress for the range investigated. Aging at 190 °C for 170 h changes neither the Ni–P structure nor the intrinsic stress to a significant degree. Further investigation indicated that the intrinsic stress was probably related to the Ni–P microstructure as a result of the deposition rate. It was found that the higher the deposition rate, the higher the intrinsic stress.